Socio-Economic Potential and Marketing Trend of Bamboo in Mizoram: A Case Study from Aizawl District - Lalremsang, Paul; Vanlalfakawma, David C.; Tripathi, S. K. (Indian Forester, 2017)
Bamboo plays an important role in the socio-economic life of rural as well as urban people. Due to its varied uses including construction of houses, huts along the roadsides for selling agricultural produce, household articles, fencing, agricultural implements, cultural implements etc. The present study was done to evaluate the pools and fluxes of bamboo culms in Aizawl and its value added products obtained in the study area. Data were collected among the bamboo entrepreneurs in the local markets using PRA and survey was conducted in three strata viz. retailer, industry and consumer level. Among all bamboo species Bambusa tulda was the most common species found in the market although Melocanna baccifera dominates among bamboo species that contributes about 95% of the growing stock in the state. Schizostachyum dulloa being the most preferred species due to its long internode and flexibility for making export products. The price of one bundle of bamboo culms varies from ` 170-200/- whereas the price of dap (flattened bamboo) varies from ` 200-250/-. The total weekly turnover of bamboo culms market in the city was ` 487,250.00/- in which 2,685 bamboo culms supplied and 1,466 bundles sold weekly. The study also reveals that bamboo culm markets provide employment for 27 male and 25 female that gives a total of 52 persons in the study area. The findings of the study will help to assess the trends of bamboo culms in the market, its socio-cultural and economic importance provided by bamboo resource in Aizawl district and the state as a whole.